Results of an Environmental Scan to Determine the Level of Uncorrected Refractive Error in First Nations Elementary School Children in Ontario - Chris, A. Paul; Young, Nancy L.; Belanger, Kayla; Greasley, Lyndsay (Canadian Journal of Optometry, 2017)
A survey was developed and used to determine the level and quality of vision care services available to First Nations elementary school children across Ontario, and to indirectly determine the level of uncorrected refractive error in First Nations children. Overall, the total survey results showed that 1 child in 4 wore glasses. The results from the survey indicated that remote communities that had a visiting optometrist were more likely to have fewer cases of uncorrected refractive error than non-remote communities. The results suggest that in-community comprehensive eye exams delivered on a regular basis by visiting optometrists would be the most effective way of improving the vision and eye health status of First Nations children.